Genetic polymorphisms in innate immunity receptors do not predict the risk of bacterial and fungal infections and acute rejection after liver transplantation. Issue 2 (13th December 2012) - de, E.L.D.; Mancham, S.; Utomo, W.K.; de, I.; van, M.; de, E.; Rossau, R.; van der, L.J.W.; Hansen, B.E.; Tilanus, H.W.; Kazemier, G.; Janssen, H.L.A.; et al.
Abstract Introduction We studied the influence of a broad range of genetic variants in recipient and donor innate immunity receptors on bacterial and fungal infections and acute rejection after liver transplantation (LT). Methods Seventy‐six polymorphisms in TLR 1‐10, NOD2, LBP, CD14, MD2, SIGIRR, Ficolins 1, ‐2, and ‐3, MASP 1, ‐2, and ‐3, and the complement receptor C1qR1 were determined in 188 LT recipients and 135 of their donors. Associations with clinically significant infections and acute rejection were analyzed for 50 polymorphisms. Significant associations were validated in an independent cohort of 181 recipients and 167 donors. Results Three recipient polymorphisms and 3 donor polymorphisms were associated with infections in the identification cohort, but none of these associations were confirmed in the validation cohort. Three donor polymorphisms were associated with acute rejection in the identification cohort, but not in the validation cohort. Conclusion In contrast to their effect in the general population, 50 common genetic variations in innate immunity receptors do not influence susceptibility to bacterial/fungal infections after LT. In addition, no reproducible associations with acute rejection after LT were observed. Likely, transplant‐related factors play a superior role as risk factors for bacterial/fungal infections and acute rejection after LT.